Analysis and Optimization of 275 kV Transmission Tower by Using Linear Static Analysis and P-Delta Analysis. - Kamarudin, Siti Aisyah; Usman, Fathoni; Che Omar, Rohayu; Mat Yatim, Mohd Yazee (International Journal of Engineering and Technology, 2018)
The increasing global population was demanded for more consumption of electricity. In Malaysia, it was reported that 17,790 megawatts (MW) was consumed in October 2017 due to high demand. The peak reading recorded is 0.011% increase compared to demand on April 2016 (17,788 MW). Following this, more transmission tower lines need to be developed to generate more electricity. Land acquisition is the main issue for constructing the new transmission tower because it requires a large area to set it up. The idea of optimization on the existing transmission tower helps in reducing cost for constructing the new structure. The aim of this study is to develop an optimal design of the transmission tower. A 275 kV transmission tower model is used in this study for analyzing and optimizing by using linear static and p-delta analysis. This optimization method is done by reducing tower members as well as increasing size of member’s element. A design calculation for modification and arrangement of the transmission tower members is referred to manual guidelines of EN1993-3-1 and ASCE 10-97. Two alternatives are being prepared to produce an optimal design and result shows that a reduction percentage in term of reduced number of bar members can be saved up to 34 %.